Implementation of A Blood Donor Information System Using Mobile Applications Gunung Kidul District - Sebastian, Danny; Sejati, Rr.Hajar Puji (International Journal Software Engineering and Computer Science (IJSECS), 2023)
Blood donation is a common charitable activity in many communities. Consequently, the Indonesian Red Cross (PMI) in the Gunung Kidul district frequently organizes such humanitarian events across various locations. However, not everyone is aware of these events or is able to participate in blood donation. The lack of information dissemination and blood donation events are significant factors contributing to the low community participation. The existing system for searching, processing, and creating data is still manual, which hinders the efficiency of administrative tasks. Addressing these issues, the aim of this research is to develop an Android-based blood donation information application. This initiative is particularly vital as the PMI in Gunung Kidul lacks the necessary infrastructure to disseminate information about the availability of blood bags efficiently. In the current era of digital advancement, the slow pace of information distribution is notably ineffective, thus integrating the system with Android technology is a strategic solution. sThis blood donation application is designed for donors who lack information about blood donation activities and for organizations wishing to conduct such events. The development of this Android application system involves experimental data collection methods, including observation, interviews, literature study, and documentation. The unit testing employs the Waterfall methodology. The application is developed using the Kotlin programming language, with the aid of Android Studio software